A Model to Share Hidden Data in Image for Military Access (Texas Journal of Engineering and Technology, 2022)
Presenting a days the information security and information, honesty are the two testing ranges for exploration. This study depicts the idea of distinct reversible information, concealing method that is connected with web security. When it is craved to send the classified/critical/secure data over an unstable and transfer speed obliged channel it is standard to scramble the spread information and after that install the private/essential/secure data into that cover information. With a scrambled picture/video containing extra data, if a beneficiary receives the data covering up key alone, he can extricate the extra information yet the picture substance is obscure to him. On the off chance that the beneficiary has the encryption key, he can unscramble to get merely a picture like the foremost one, notwithstanding the extra information can't be taken. On the off chance that the collector has both the information stowing away key and the encryption key, he can split both the excess information and recoup the first flick with no blunder by misusing the spatial connection in regular picture. In the present technique the information takes cover behind the movies, the interlopers can without much of a stretch procure this data in light of the fact that it is not scrambled. In this paper, we have made up a method to hide information in Encrypted pictures. This paper designs to contribute a review of image steganography and picture encryption, its habits and methods. In the proposed framework we are encoding the information utilizing the Rijndeal calculation which is additionally used by the Military powers. This calculation conceals the information in the picture using the LSB strategy and the picture is again scrambled utilizing the RSA calculation. For this whole encryption prepares the client receives a secret word. After the encoding process is finished the sender transmits the record to the accumulator. The collector can extricate the information only on the off chance that he is sustained during the time spent laughing.